Multispacecraft Observations of a Widespread Solar Energetic Particle Event on 2022 February 15–16 - Khoo, L. Y. (Institute of Physics Publishing, 2025)
On 2022 February 15–16, multiple spacecraft measured one of the most intense solar energetic particle (SEP) events observed so far in Solar Cycle 25. This study provides an overview of interesting observations made by multiple spacecraft during this event. Parker Solar Probe (PSP) and BepiColombo were close to each other at 0.34–0.37 au (a radial separation of ∼0.03 au) as they were impacted by the flank of the associated coronal mass ejection (CME). At about 100° in the retrograde direction and 1.5 au away from the Sun, the radiation detector on board the Curiosity surface rover observed the largest ground-level enhancement on Mars since surface measurements began. At intermediate distances (0.7–1.0 au), the presence of stream interaction regions (SIRs) during the SEP arrival time provides additional complexities regarding the analysis of the distinct contributions of CME-driven versus SIR-driven events in observations by spacecraft such as Solar Orbiter and STEREO-A, and by near-Earth spacecraft like ACE, SOHO, and WIND. The proximity of PSP and BepiColombo also enables us to directly compare their measurements and perform cross-calibration for the energetic particle instruments on board the two spacecraft. Our analysis indicates that energetic proton measurements from BepiColombo and PSP are in reasonable agreement with each other to within a factor of ∼1.35. Finally, this study introduces the various ongoing efforts that will collectively improve our understanding of this impactful, widespread SEP event.